Effects of the SLCO1B1 *1 and SLCO1B1 *5 polymorphisms on IL-6 and IL-10 levels in patients under pravastatin treatment prior to inguinal hernia repair. (March 2016) - Cárdenas-Rojas, Martha Irazema; Delgado-Enciso, Ivan; Baltazar-Rodríguez, Luz Margarita; Guzmán-Esquivel, José; Ramírez-Flores, Mario
Abstract: Background: Different genetic variants in the SLCO1B1 gene have been shown to have functional importance in individual variability in pravastatin pharmacokinetics, resulting in different inflammatory responses to surgical inguinal hernia repair. The aim of this study was to determine IL-6 and IL-10 serum concentrations in the presence and absence of the SLCO1B1*1 and SLCO1B1*5 polymorphisms in patients under pravastatin treatment that underwent inguinal hernia repair. Methods: The study included 26 subjects that were under pravastatin treatment (40 mg/day) at least 1 month prior to inguinal hernia repair open technique. All the subjects were genotyped for the SLCO1B1*1 and SLCO1B1*5 polymorphisms through polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and their preoperative and postoperative serum IL-6 and IL-10 levels were quantified through the ELISA technique. The IL-6 and IL-10 levels were analyzed in the presence or absence of the mutated polymorphism for SLCO1B1*1 and SLCO1B1*5 . Results: The SLCO1B1*1 polymorphism had a frequency of 38.5% and the SLCO1B1*5 polymorphism had a frequency of 19.2%. The preoperative and postoperative serum concentrations of IL-6 were 0.252 pg/ml ± 0.19 and 0.206 pg/ml ± 0.20, respectively, with a p = 0.525, whereas the preoperative and postoperative serum concentrations for IL-10 were 4.943 pg/ml ± 3.13 and 4.611 pg/ml ± 3.01, respectively, with a p = 0.004. Conclusions: The patients under pravastatin treatment presented with lower postoperative IL-10 levels with respect to the baseline concentration (p = 0.004), regardless of the presence or absence of the two polymorphisms. Highlights: The presence of SLCO1B1*1 and SLCO1B1*5 polymorphisms could alter the transport of drugs. Pravastatin inhibits the 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase. The SLCO1B1*1 polymorphism had a frequency of 38.5% in a Mexican population. The SLCO1B1*5 polymorphism had a frequency of 19.2% in a Mexican population. The presence of the SLCO1B1*5 polymorphism had a greater influence on IL-10 levels.